(3TQM CUhd GdTGWHjIs - (3UObI Hf SdGeI Hf MSjfs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3CfJ GdMHjH heGdj Yfc SdhGf hajc VM Ydj GdCfS hGdLGf Hjfj s
(3BNQgG (B:s
(3hgfGc aJM GdOGd hgfG EScGf CdakG ef ZjQ Cda s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B74s
(3GdfSNI HgG MhGTs
(3HChdg ahGFO hHBNQg agQSJ eUfaGJ CHj YeQh GdOGfjs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
Keywords: (3GdbQGAGJ hGdJLhjOs